Clima organizacional y desempeño laboral de los colaboradores del área de administración de Electro Oriente, Iquitos 2023 - Rodriguez Flores, Roxy Ariel (2023)
As a general objective of this research work we have "Determine how the organizational climate is related to the work performance of employees in the administration area of Electro Oriente, Iquitos 2023." It is also recognized that it is descriptive, correlational, quantitative that describes the development of events, the value is 0.484** Pearson, this would indicate that there is a weak positive correlation between the first and second variable. In conclusion, there is a relationship between the first and second variable.